DIAGNÓSTICO DE RIESGOS PSICOSOCIALES DE LOS SERVIDORES PÚBLICOS EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO DEL CANTÓN CHAGUARPAMBA, PERIODO 2023. - Madero Carrión, David Alejandro (2024)
The following research work aims to present an assessment of the psychosocial risks to which public servants of the Autonomous Decentralized Government of the Canton of Chaguarpamba are exposed in the year 2023. This study has taken into account Robert Karasek's demand-control theory, which focuses on psychosocial risks at work. In order to gather information quantitatively, the Ministry of Labor prepared a psychosocial risks questionnaire, which was administered to 61 public servants at the GAD; thus, sampling was not used since there were only a few number of employees. According to the results of the survey, the risk in the institution is considered to be of minimal potential impact, as 87% of employees surveyed indicated that there is a low risk, and none indicated that there is a high risk. As a result, it is important to monitor occupational health on a periodic basis, so a psychosocial risk prevention plan is being considered in order to mitigate the harmful effects on the welfare of servers.